Multi-component molten salt heat storage material and preparation method thereof
By combining modified sodium nitrate nanocomposites with SiO2/Al2O3/EG composites, sodium carbonate and sodium nitrite are generated by solution combustion to form a five-membered mixed molten salt system, which solves the thermal conductivity of inorganic phase change heat storage materials The problem of low is that composite phase change materials with high thermal conductivity and high energy storage density are achieved, improving thermal stability and operating temperature range.
Patent Information
- Application Number
- CN202411297673.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
The low thermal conductivity of inorganic phase change heat storage materials limits their application in the industrial field, and it is more challenging to improve thermal conductivity and energy storage density.
Modified sodium nitrate nanocomposite is combined with SiO2/Al2O3/EG composite material, and sodium nitrite is generated by solution combustion to form a five-membered mixed molten salt system, increasing porosity and improving thermal conductivity, forming a high Composite phase change material with thermal conductivity and high energy storage density.
The thermal conductivity and thermal diffusion coefficient of the material are significantly improved, thermal stability and thermal durability are enhanced, while forming a low corrosion and a wider operating temperature range.
Smart Images

Figure BDA0005046574330000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat transfer and energy storage materials, and in particular to a multi-component molten salt heat storage material and a preparation method thereof. Background Art
[0002] In order to improve energy efficiency, energy storage technology has become a hot research field. Among various forms of energy storage, thermal energy storage (TES) has received more and more attention in the energy field. According to the classification of heat storage methods, TES mainly includes sensible heat storage, latent heat storage and thermochemical heat storage. One of the core of heat storage technology is heat storage materials, and phase change heat storage materials (PCM) are an important part of latent heat storage technology. The research on phase change heat storage materials is of great significance to the efficient utilization of energy.
[0003] PCM has been applied in many fields such as solar energy utilization, industrial waste heat recovery, and building energy conservation. In the classification of PCM, inorganic materials have the characteristics of wide operating temperature range, high heat storage density, and good thermal stability. Inorganic PCM mainly includes hydrated salts and inorganic molten salts. The most common inorganic molten salts are nitrates, chlorides, carbonates, fluorides, etc. In order to meet different thermal storage temperature requirements, researchers usually mix different inorganic molten salts together. As a thermal storage material, nitrates have excellent thermal properties, carbonates and chlorides can adapt to higher operating temperatures, and nitrate / nitrite mixed molten salts have low corrosiveness, lower melting points, and higher upper temperature limits.
[0004] However, both inorganic PCM and organic PCM have the problem of low thermal conductivity, which greatly limits the application of such materials in the industrial field. Studies have shown that the thermal conductivity of phase change materials can be improved by high thermal conductivity additives and microencapsulation. Commonly used additives include high thermal conductivity nanoparticles, foamed graphite and metal foam. The thermal conductivity of expanded graphite-based composite phase change materials depends on the mass fraction, bulk density, aspect ratio, surface area and thickness of expanded graphite. Metal foam has the advantages of good stability and low density, so it performs better than nanoparticles in enhancing thermal conductivity. However, the porosity of the foam has a great influence on the performance of the composite phase change material. High porosity foam is conducive to improving the thermal storage capacity of the phase change material, but the thermal conductivity is not greatly improved; low porosity foam can greatly improve the thermal conductivity of the phase change material, but it will reduce its heat storage capacity. Therefore, it is quite challenging to develop a composite phase change material with high thermal conductivity and high energy storage density at the same time. Summary of the invention
[0005] The object of the present invention is to provide a multi-component molten salt thermal storage material and a preparation method thereof to solve the problems raised in the background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a multi-component molten salt thermal storage material comprises the following steps:
[0008] The modified sodium nitrate nanocomposite material, lithium nitrate and sodium chloride are placed in a stainless steel mortar and ground into powder. The mixed molten salt is then poured into a corundum crucible in a muffle furnace, heated to 370-400°C, and kept at 370-400°C for 2-3 hours. The furnace is cooled to 100-140°C, the sample is taken out and naturally cooled to room temperature, the cooled molten salt is placed in a grinder and crushed to obtain a mixed molten salt powder, which is then placed in an oven and dried at 80-90°C for 12 hours to obtain a multi-component molten salt thermal storage material.
[0009] Furthermore, the mass ratio of the modified sodium nitrate nanocomposite material, lithium nitrate and sodium chloride is 85-90:8-10:2-5.
[0010] Furthermore: the heating rate of the muffle furnace is 5°C / min.
[0011] Furthermore: the particle size of the mixed molten salt powder is 20-200 mesh.
[0012] Further: The preparation method of the modified sodium nitrate nanocomposite material is:
[0013] S1. Aluminum tri-sec-butoxide was dissolved in deionized water at 90°C, and a 5% nitric acid aqueous solution was added dropwise thereto until the pH value was 2-3. The solution was stirred continuously at 90°C for 4 hours, and then expanded graphite was added and stirred evenly. The sample was transferred to a crucible, calcined at 300°C for 1 hour, and naturally cooled to obtain an Al2O3 / EG composite material;
[0014] S2, adding sodium silicate and Al2O3 / EG composite material to a mixture of water and ethanol, mixing with a magnetic stirrer at room temperature for 2 hours, adding acetic acid dropwise to the mixture, adjusting the pH value of the solution to 4.5, stirring at room temperature for 2 hours, filtering and collecting the product, washing with water and ethanol, and drying at 200°C for 24 hours to obtain a SiO2 / Al2O3 / EG composite material;
[0015] S3. Mix NaNO3, citric acid, deionized water and SiO2 / Al2O3 / EG composite material in a crucible, heat the mixture from room temperature to 400°C at a rate of 10°C / min in a muffle furnace, heat at 400°C for 4h, pour out at 280°C, and cool to room temperature to obtain a modified sodium nitrate nanocomposite material.
[0016] It should be noted that the hierarchical pore structure of the Al2O3 / EG composite material can significantly improve the thermal conductivity and thermal diffusion coefficient of the organic phase change thermal storage material, and the hydrophilicity of the Al2O3 / EG composite material is improved due to the presence of multiple silanol groups in the anchored SiO2. The SiO2 / Al2O3 / EG composite material was then used as a ternary porous carrier for adsorbing and stabilizing the multi-component molten salt system to form a composite phase change material for thermal energy storage. The solution combustion method was used to configure the excess sodium nitrate and citric acid into a solution, so that the base salt and the fuel were fully and evenly mixed, and the sodium nitrate was modified to generate sodium carbonate. Sodium nitrite also released carbon dioxide and nitrogen dioxide gas. The gas can increase the pores of the SiO2 / Al2O3 / EG composite material, and adsorb sodium nitrate, sodium carbonate and sodium nitrite into the pore structure, which can well seal these salts to prevent them from leaking. In addition, the reaction has nano-scale carbon generation, which can increase the thermal conductivity of nitrates, enhance the heat storage capacity of molten salts, and improve its thermal stability and thermal durability.
[0017] Further: in step S1, the mass ratio of aluminum tri-sec-butoxide, deionized water and EG is 3-5:10-15:0.2.
[0018] Furthermore: in step S2, the usage ratio of water, ethanol, sodium silicate and Al2O3 / EG composite material is 70mL:30mL:2-4g:0.2-0.3g.
[0019] Furthermore: in step S3, the mass ratio of NaNO3, citric acid, deionized water and SiO2 / Al2O3 / EG composite material is 4-6:1-2:10:1-2.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The hierarchical pore structure of the Al2O3 / EG composite material can significantly improve the thermal conductivity and thermal diffusion coefficient of the organic phase change thermal storage material, which is conducive to the subsequent formation of a composite phase change material with high thermal conductivity and high energy storage density. The polycondensation and over-aggregation of SiO2 on the surface of expanded graphite enable the formation of a highly interconnected porous network. In addition, the presence of multiple silanol groups in the anchored SiO2 improves the hydrophilicity of the Al2O3 / EG composite material and enhances its adsorption capacity. The SiO2 / Al2O3 / EG composite material was subsequently used as a ternary porous carrier for the adsorption and stabilization of a multi-component molten salt system.
[0022] (2) Solution combustion method: Excess sodium nitrate and citric acid are prepared into a solution, so that the base salt and the fuel are fully and evenly mixed, and the sodium nitrate is modified to generate sodium carbonate. Sodium nitrite also releases carbon dioxide and nitrogen dioxide gases. The gases can increase the pores of the SiO2 / Al2O3 / EG composite material and adsorb sodium nitrate, sodium carbonate and sodium nitrite into the pore structure to seal them and prevent them from leaking. In addition, the reaction generates nano-scale carbon, which can increase the thermal conductivity of nitrates, enhance the heat storage capacity of molten salts, and improve their thermal stability and thermal durability.
[0023] (3) The sodium nitrite and sodium carbonate produced in the above reaction form a five-component mixed molten salt system with sodium nitrate, lithium nitrate and sodium chloride, which has better thermophysical properties and a wider operating temperature range, as well as low corrosiveness, a lower melting point and a higher heat storage density. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Preparation method of modified sodium nitrate nanocomposite material:
[0026] S1. Dissolve 3.5 g of aluminum tri-sec-butoxide in 12 mL of deionized water at 90° C., add a 5% nitric acid aqueous solution dropwise thereto until the pH value is 2.5, stir the solution continuously at 90° C. for 4 h, add 0.2 g of expanded graphite, stir evenly, transfer the sample to a crucible, calcine at 300° C. for 1 h, and cool naturally to obtain an Al2O3 / EG composite material;
[0027] S2, to a mixture of 70 mL of water and 30 mL of ethanol, 2.8 g of sodium silicate and 0.25 g of Al2O3 / EG composite material were added, and the mixture was mixed with a magnetic stirrer at room temperature for 2 h, acetic acid was added dropwise to the mixture, the pH value of the solution was adjusted to 4.5, and the mixture was stirred at room temperature for 2 h, the product was collected by filtration, washed with water and ethanol, and dried at 200°C for 24 h to obtain a SiO2 / Al2O3 / EG composite material;
[0028] S3. Mix 4.2 g NaNO3, 2.8 g citric acid, 10 mL deionized water and 1.1 g SiO2 / Al2O3 / EG composite material into a crucible, heat the mixture from room temperature to 400°C at a rate of 10°C / min in a muffle furnace, heat at 400°C for 4 h, pour out at 280°C, and cool to room temperature to obtain a modified sodium nitrate nanocomposite material.
[0029] Preparation method of sodium nitrate nanocomposite material:
[0030] S1. Dissolve 3.5 g of aluminum tri-sec-butoxide in 12 mL of deionized water at 90° C., add a 5% nitric acid aqueous solution dropwise thereto until the pH value is 2.5, stir the solution continuously at 90° C. for 4 h, add 0.2 g of expanded graphite, stir evenly, transfer the sample to a crucible, calcine at 300° C. for 1 h, and cool naturally to obtain an Al2O3 / EG composite material;
[0031] S2, to a mixture of 70 mL of water and 30 mL of ethanol, 2.8 g of sodium silicate and 0.25 g of Al2O3 / EG composite material were added, and the mixture was mixed with a magnetic stirrer at room temperature for 2 h, acetic acid was added dropwise to the mixture, the pH value of the solution was adjusted to 4.5, and the mixture was stirred at room temperature for 2 h, the product was collected by filtration, washed with water and ethanol, and dried at 200°C for 24 h to obtain a SiO2 / Al2O3 / EG composite material;
[0032] S3. Mix 4.2 g NaNO3, 10 mL deionized water and 1.1 g SiO2 / Al2O3 / EG composite material into a crucible, heat the mixture from room temperature to 400°C at a rate of 10°C / min in a muffle furnace, heat at 400°C for 4 h, pour out at 280°C, and cool to room temperature to obtain a sodium nitrate nanocomposite material.
[0033] Example 1
[0034] 87.2g of modified sodium nitrate nanocomposite material, 8.5g of lithium nitrate and 4.1g of sodium chloride were placed in a stainless steel mortar and ground into powder. The mixed molten salt was then poured into a corundum crucible in a muffle furnace, heated to 370°C at a heating rate of 5°C / min, and kept at 370°C for 2h. The furnace was cooled to 140°C, the sample was taken out and naturally cooled to room temperature, the cooled molten salt was placed in a grinder and crushed to obtain a mixed molten salt powder, which was then placed in an oven and dried at 90°C for 12h to obtain a multi-component molten salt thermal storage material.
[0035] Example 2
[0036] 89.5 g of modified sodium nitrate nanocomposite material, 9.0 g of lithium nitrate and 4.5 g of sodium chloride were placed in a stainless steel mortar and ground into powder. The mixed molten salt was then poured into a corundum crucible in a muffle furnace, heated to 380 ° C at a heating rate of 5 ° C / min, and kept at 380 ° C for 2.5 h. The furnace was cooled to 130 ° C, the sample was taken out and naturally cooled to room temperature, the cooled molten salt was placed in a grinder and crushed to obtain a mixed molten salt powder, which was then placed in an oven and dried at 80 ° C for 12 h to obtain a multi-component molten salt thermal storage material.
[0037] Example 3
[0038] 85.2g of modified sodium nitrate nanocomposite material, 8.0g of lithium nitrate and 3.9g of sodium chloride were placed in a stainless steel mortar and ground into powder. The mixed molten salt was then poured into a corundum crucible in a muffle furnace, heated to 400°C at a heating rate of 5°C / min, and kept at 400°C for 2h. The furnace was cooled to 140°C, the sample was taken out and naturally cooled to room temperature, the cooled molten salt was placed in a grinder and crushed to obtain a mixed molten salt powder, which was then placed in an oven and dried at 90°C for 12h to obtain a multi-component molten salt thermal storage material.
[0039] Example 4
[0040] 88.6 g of modified sodium nitrate nanocomposite material, 8.8 g of lithium nitrate and 5.0 g of sodium chloride were placed in a stainless steel mortar and ground into powder. The mixed molten salt was then poured into a corundum crucible in a muffle furnace, heated to 390 ° C at a heating rate of 5 ° C / min, and kept at 390 ° C for 3 hours. The furnace was cooled to 130 ° C, the sample was taken out and naturally cooled to room temperature, the cooled molten salt was placed in a grinder and crushed to obtain a mixed molten salt powder, which was then placed in an oven and dried at 85 ° C for 12 hours to obtain a multi-component molten salt thermal storage material.
[0041] Comparative Example 1
[0042] 87.2g of sodium nitrate nanocomposite material, 8.5g of lithium nitrate and 4.1g of sodium chloride were placed in a stainless steel mortar and ground into powder. The mixed molten salt was then poured into a corundum crucible in a muffle furnace, heated to 370°C at a heating rate of 5°C / min, and kept at 370°C for 2h. The furnace was cooled to 140°C, the sample was taken out and naturally cooled to room temperature, the cooled molten salt was placed in a grinder and crushed to obtain a mixed molten salt powder, which was then placed in an oven and dried at 90°C for 12h to obtain a multi-component molten salt thermal storage material.
[0043] Comparative Example 2
[0044] 87.2g of sodium nitrate, 8.5g of lithium nitrate, 4.1g of sodium chloride and 24.2g of expanded graphite were placed in a stainless steel mortar and ground into powder. The mixed molten salt was then poured into a corundum crucible in a muffle furnace, heated to 370°C at a heating rate of 5°C / min, and kept at 370°C for 2h. The furnace was cooled to 140°C, the sample was taken out and naturally cooled to room temperature, the cooled molten salt was placed in a grinder and crushed to obtain a mixed molten salt powder, which was then placed in an oven and dried at 90°C for 12h to obtain a multi-component molten salt thermal storage material.
[0045] Comparative Example 3
[0046] 87.2g of sodium nitrate, 8.5g of lithium nitrate and 4.1g of sodium chloride were placed in a stainless steel mortar and ground into powder. The mixed molten salt was then poured into a corundum crucible in a muffle furnace, heated to 370°C at a heating rate of 5°C / min, and kept at 370°C for 2h. The furnace was cooled to 140°C, the sample was taken out and naturally cooled to room temperature, the cooled molten salt was placed in a grinder and crushed to obtain a mixed molten salt powder, which was then placed in an oven and dried at 90°C for 12h to obtain a multi-component molten salt thermal storage material.
[0047] The thermal constant analyzer obtains thermal conductivity and thermal diffusivity. Before measurement, the test sample needs to be pressed using a powder tablet press with a molding pressure of 10 MPa. During measurement, the test probe is placed between two samples of the same specification for measurement.
[0048] The main heat storage properties of the samples were tested using a differential scanning calorimeter with a temperature measurement accuracy of ±0.1°C and a calorimetric accuracy of ±1%. The sample mass for each test was controlled within 5-20 mg. The measurement conditions of the prepared materials were: test temperature range: 100-350°C; heating rate: 10°C / min.
[0049] The test results of the embodiments and comparative examples are shown in Table 1.
[0050] Table 1
[0051]
[0052]
[0053] As shown in Table 1, compared with Comparative Examples 1-3, the multi-component molten salt thermal storage materials prepared in Examples 1-4 have sodium nitrite, sodium carbonate, carbon structure grown on the particle surface derived from sodium nitrate modified by citric acid, and the interaction between gas and SiO2 / Al2O3 / EG composite material, which improves the thermal conductivity, thermal energy storage efficiency and specific heat capacity of the material, which is manifested in the high thermal stability and heat transfer coefficient of the material itself and the low corrosiveness and wider operating temperature range as a thermal storage material. Although Comparative Example 1 adds SiO2 / Al2O3 / EG composite material and forms a highly interconnected porous network, its ability to adsorb inorganic salts is poor compared with the embodiment, and a multi-component molten salt system of nitrate, nitrate, carbonate and sodium chloride is not formed, resulting in poor thermal physical properties of the material. Comparative Example 2 only adds a nanomaterial of expanded graphite, which is worse than Comparative Example 1 in its ability to adsorb inorganic salts. Comparative Example 3 does not add nanomaterials with adsorption effects, which may cause leakage of phase change materials.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a multi-component molten salt thermal storage material, characterized in that: The following steps are involved: The modified sodium nitrate nanocomposite material, lithium nitrate and sodium chloride are placed in a stainless steel mortar and ground into powder. The mixed molten salt is then poured into a corundum crucible in a muffle furnace, heated to 370-400°C, and kept at 370-400°C for 2-3 hours. The furnace is cooled to 100-140°C, the sample is taken out and naturally cooled to room temperature, the cooled molten salt is placed in a grinder and crushed to obtain a mixed molten salt powder, which is then placed in an oven and dried at 80-90°C for 12 hours to obtain a multi-component molten salt thermal storage material.
2. The method for preparing a multi-component molten salt thermal storage material according to claim 1, characterized in that: The mass ratio of the modified sodium nitrate nanocomposite material, lithium nitrate and sodium chloride is 85-90:8-10:2-5.
3. The method for preparing a multi-component molten salt thermal storage material according to claim 1, characterized in that: The heating rate of the muffle furnace is 5°C / min.
4. The method for preparing a multi-component molten salt thermal storage material according to claim 1, characterized in that: The particle size of the mixed molten salt powder is 20-200 meshes.
5. The method for preparing a multi-component molten salt thermal storage material according to claim 1, characterized in that: The preparation method of the modified sodium nitrate nanocomposite material is as follows: S1. Aluminum tri-sec-butoxide was dissolved in deionized water at 90°C, and a 5% nitric acid aqueous solution was added dropwise thereto until the pH value was 2-3. The solution was stirred continuously at 90°C for 4 hours, and then expanded graphite was added and stirred evenly. The sample was transferred to a crucible, calcined at 300°C for 1 hour, and naturally cooled to obtain an Al2O3 / EG composite material; S2, adding sodium silicate and Al2O3 / EG composite material to a mixture of water and ethanol, mixing with a magnetic stirrer at room temperature for 2 hours, adding acetic acid dropwise to the mixture, adjusting the pH value of the solution to 4.5, stirring at room temperature for 2 hours, filtering and collecting the product, washing with water and ethanol, and drying at 200°C for 24 hours to obtain a SiO2 / Al2O3 / EG composite material; S3. Mix NaNO3, citric acid, deionized water and SiO2 / Al2O3 / EG composite material in a crucible, heat the mixture from room temperature to 400°C at a rate of 10°C / min in a muffle furnace, heat at 400°C for 4h, pour out at 280°C, and cool to room temperature to obtain a modified sodium nitrate nanocomposite material.
6. The method for preparing a multi-component molten salt thermal storage material according to claim 5, characterized in that: In the step S1, the mass ratio of aluminum tri-sec-butoxide, deionized water and EG is 3-5:10-15:0.
2.
7. The method for preparing a multi-component molten salt thermal storage material according to claim 5, characterized in that: In the step S2, the usage ratio of water, ethanol, sodium silicate and Al2O3 / EG composite material is 70mL:30mL:2-4g:0.2-0.3g.
8. The method for preparing a multi-component molten salt thermal storage material according to claim 5, characterized in that: The mass ratio of NaNO3, citric acid, deionized water and SiO2 / Al2O3 / EG composite material in step S3 is 4-6:1-2:10:1-2.
9. A multi-component molten salt thermal storage material obtained by the preparation method according to any one of claims 1 to 8.
